Oral Delivery of Nisin in Resistant Starch Based Matrices Alters the Gut Microbiota in Mice - Gough, Ronan; Cabrera Rubio, Raúl; O'Connor, Paula M.; Crispie, Fiona; Brodkorb, André; Miao, Song; Hill, Colin; Ross, Reynolds P.; Cotter, Paul D.; Nilaweera, Kanishka N.; Rea, Mary C. (Frontiers in Microbiology, 2018)
There is a growing recognition of the role the gastrointestinal microbiota plays in health and disease. Ingested antimicrobial proteins and peptides have the potential to alter the gastrointestinal microbiota; particularly if protected from digestion. Nisin is an antimicrobial peptide that is used as a food preservative. This study examined the ability of nisin to affect the murine microbiota when fed to mice in two different starch based matrices; a starch dough comprising raw starch granules and a starch gel comprising starch that was gelatinized and retrograded. The effects of the two starch matrices by themselves on the microbiota were also examined. Following 16S rRNA compositional sequencing, beta diversity analysis highlighted a significant difference (p = 0.001, n = 10) in the murine microbiota between the four diet groups. The differences between the two nisin containing diets were mainly attributable to differences in the nisin release from the starch matrices while the differences between the carriers were mainly attributable to the type of resistant starch they possessed. Indeed, the differences in the relative abundance of several genera in the mice consuming the starch dough and starch gel diets, in particular Akkermansia, the relative abundance of which was 0.5% and 11.9%, respectively (p = 0.0002, n = 10) points to the potential value of resistance starch as a modulator of beneficial gut microbes. Intact nisin and nisin digestion products (in particular nisin fragment 22-31) were detected in the feces and the nisin was biologically active. However, despite a threefold greater consumption of nisin in the group fed the nisin in starch dough diet, twice as much nisin was detected in the feces of the group which consumed the nisin in starch gel diet. In addition, the relative abundance of three times as many genera from the lower gastrointestinal tract (GIT) were significantly different (p < 0.001, n = 10) to the control for the group fed the nisin in starch gel diet, implying that the starch gel afforded a degree of protection from digestion to the nisin entrapped within it.